Valencia en el Cancionero general de Hernando del Castillo: los poetas y los poemas - Perea Rodríguez, Óscar (Dicenda. Estudios de lengua y literatura españolas, 2003)
This present study focuses about biographies of Valencia’s poets, which are on Hernando del Castillo’s Cancionero general. In the same way, poems which include typical Valencia’s themes are also analyzed, in order to stimulate a much more knowledge about city, kingdom and men in whose cultural and courtly scene Castillo’s Cancionero general grew up.